Report on the training needs survey - women in small business in Jamaica - National Development Foundation of Jamaica (National Development Foundation of Jamaica KingstonJA)
Analyses the training needs of Jamaican women, and assesses the validity and reliability of existing data. Identifies areas in which training programmes could bring most benefit to female entrepreneurs. Forms the basis for the development of specialized training programmes.